Directional enhancement of 2-keto-gluconic acid production from enzymatic hydrolysate by acetic acid-mediated bio-oxidation with Gluconobacter oxydans. (March 2022) - Dai, Lin; Jiang, Wenfei; Jia, Runqian; Zhou, Xin; Xu, Yong
Highlights: HAc could promote 2-KGA accumulation in the process of glucose with G. oxydans. The yield of 2-KGA was increased from 38.0% to 80.5% with addition of 5 g/L HAc. A 2-KGA yield of 83.5% was achieved using enzymatic hydrolysate as feedstock. Abstract: An acetic acid-mediated bio-oxidation strategy with Gluconobacter oxydans was developed to produce valuable 2-ketogluconic acid from lignocellulosic biomass. Metabolically, glucose is firstly oxidized to gluconic acid and further oxidized to 2-keto-gluconic acid by Gluconobacter oxydans . As a specific inhibitor for microbial fermentation generated from pretreatment, acetic acid was validated to have a down-regulated effect on bio-oxidizing glucose to gluconic acid. Nevertheless, it significantly facilitated 2-keto-gluconic acid accumulation and improved gluconate dehydrogenase activity. In the presence of 5.0 g/L acetic acid, the yield of 2-keto-gluconic acid increased from 38.0% to 80.5% using pure glucose as feedstock with 1.5 g/L cell loading. Meanwhile, 44.6 g/L 2-keto-gluconic acid with a yield of 83.5% was also achieved from the enzymatic hydrolysate. 2-keto-gluconic acid production, found in this study, laid a theoretical foundation for the industrial production of 2-keto-gluconic acid by Gluconobacter oxydans using lignocellulosic materials.